2012
DOI: 10.1177/0884533611436115
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Blind Randomized Study Comparing the Efficacy and Safety of a Composite vs a Conventional Intravenous Fat Emulsion in Postsurgical Gastrointestinal Tumor Patients

Abstract: composite IVFE was comparable with conventional LCT/MCT IVFE in efficacy, safety, tolerance, and clinical outcomes in surgical GI tumor patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…Given the potential to reduce thrombosis, studies of platelet function with parenteral fish oil have been undertaken in adult humans, particularly in the setting of surgical interventions 16 . ‐ 19 While these studies have been reassuring, it must be noted that the doses are markedly lower than those advocated for infants with IFALD given PN exclusively with fish oil.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential to reduce thrombosis, studies of platelet function with parenteral fish oil have been undertaken in adult humans, particularly in the setting of surgical interventions 16 . ‐ 19 While these studies have been reassuring, it must be noted that the doses are markedly lower than those advocated for infants with IFALD given PN exclusively with fish oil.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current data available for Smoflipid are from short‐term clinical trials (Table 1), 91 103 the use of MO IFE is theoretically much more physiologically similar to normal dietary human consumption and human milk (Table 2). 19 , 96 , 101 , 102 , 104 105 It appears to use the advantages of each oil while reducing the disadvantages (ie, SO and inflammation, FO and low number of calories, respectively) of relying predominately on 1 oil for the IFE source. The benefits of this approach seem especially evident in the impact of IFEs on liver enzymes, with multiple studies showing either a decrease or a smaller increase with MO IFE use 91 – 93 , 95 , 98 – 100 .…”
Section: Mixed‐oil Ifementioning
confidence: 99%
“…Regarding the rest of clinical studies, six (46%) resulted in similar clearance to control emulsions (6,14,16,20,30,34), and only in one (8%) of them (7) triglyceridemia increased in the experimental group.…”
Section: Effects Unrelated To Anti-inflammation Of Lipid Emulsions Comentioning
confidence: 99%
“…Several prospective studies have been published assessing the preventive effect of IVLEs containing FO on alterations in LETs or PNALD (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Characteristics of these studies are shown in table I.…”
Section: Potential Benefits Prevention Of Alterations In Liver Enzymementioning
confidence: 99%
See 1 more Smart Citation